1996
DOI: 10.1002/etc.5620150512
|View full text |Cite
|
Sign up to set email alerts
|

Relative mobilities of atrazine, five atrazine degradates, metolachlor, and simazine in soils of iowa

Abstract: Abstract-The relative mobilities of atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine), five atrazine degradates, metolachlor (2-chloro-N-[2-ethyl-5-methylphenyl]-N-[2-methoxy-1-methylethyl]-acetamide), and simazine (2-chloro-4,6-bis-[ethylamino]-s-triazine) were determined in both surface and subsurface soils from five locations in Iowa by soil thin-layer chromatography (STLC). Based on mobility of the compounds, four groups were identified from this study. Deethylatrazine (2-chloro-4-amino-6-isopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Relative mobilities of ATR, DEA, DIA, DDA, and HYA were also assessed in our laboratory by using STLC [10]. Surface and subsurface soils from the five locations in Iowa mentioned previously (Table 1 ) were used in this study.…”
Section: Mobilities Of Atr and Atr Dégradâtesmentioning
confidence: 99%
“…Relative mobilities of ATR, DEA, DIA, DDA, and HYA were also assessed in our laboratory by using STLC [10]. Surface and subsurface soils from the five locations in Iowa mentioned previously (Table 1 ) were used in this study.…”
Section: Mobilities Of Atr and Atr Dégradâtesmentioning
confidence: 99%
“…Metolachlor and its metabolites are also slightly mobile in soil (8); in several leaching studies, approximately 1% of applied metolachlor leached through soil columns, while selected metolachlor degradates appeared to be more mobile in soil (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Although the relative mobility of DEHYA was not determined in the soil TLC study mentioned (Kruger et al, 1996), it would likely be less mobile than DEA inasmuch as two other hydroxy s-triazine analogues (hydroxyatrazine and ammeline) were less mobile than DEA in that study. Russell et al (1968) indicated that the protonated hydroxy species of s-triazines is bound to clay, which may restrict vertical movement and entrance into groundwater.…”
Section: Discussionmentioning
confidence: 74%
“…Only a partial displacement of soil water occurs with each addition of rainfall (Thomas and Phillips, 1979). In a study comparing relative mobilities of ATR and degradates using soil TLC (Kruger et al, 1996), DDA and ATR exhibited similar mobilities, and both were significantly less mobile than DEA in this soil type. Therefore, DDA formed in surface or subsurface soils would move through the soil matrix at a slower rate than DEA.…”
Section: Discussionmentioning
confidence: 98%